Reforming Public Sector Bureaucracy: A Systematic Literature Review of New Public Management in Indonesia - Nikki Prafitri; Arenawati; Ni Made Ayu Puspa Karini; Najla Assyifa Zahrani (Future Science, 2025)
New Public Management (NPM) is a model that applies business styles to the public sector with the aim of increasing effectiveness and efficiency. The implementation of NPM based on literature studies is most widely applied in developed countries. The adoption of NPM is demonstrated by the implementation of performance-based and measurable programs or work. Indonesia has also adopted the NPM model in several areas, although there are gaps in analysis. This is because there are still limited specific case studies that reflect the implementation of the NPM model in Indonesia. This research method uses systematic literature review. The primary data source was the Scopus database, where a search was conducted using the keywords